2013
DOI: 10.1371/journal.pone.0074966
|View full text |Cite
|
Sign up to set email alerts
|

Effects of apoE Deficiency and Occlusal Disharmony on Amyloid-Beta Production and Spatial Memory in Rats

Abstract: Amyloid-β (Aβ) plays a causative role in Alzheimer’s disease. Apolipoprotein E (apoE) is involved in Aβ accumulation, whereas occlusal disharmony increases Aβ production in the rat hippocampus. The purpose of the present study was to investigate the effects of apoE deficiency and occlusal disharmony on Aβ production and spatial memory. Wild-type (WT) (n = 12) and apoE-deficient [ApoE(−/−)] (n = 12) rats (Sprague-Dawley; 8 weeks old) were used. These rats were randomly divided into four groups of six rats each:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 54 publications
0
21
0
Order By: Relevance
“…14 These findings also corroborate to another study by Okihara, et al 7 (2014), which found a memory impairment accompanied by low number of neuron cells in the hippocampus after long-term soft diet. 7 Previous studies on mastication impaired animal models through tooth extraction 22 , 23 , bite-raise 24 , 25 and long-term soft diets 7 , 26 found that these aspects may alter hippocampus learning and memory function. Other studies also proved that impaired function of the hippocampus due to long-term soft diet could be improved by providing a hard diet.…”
Section: Discussionmentioning
confidence: 99%
“…14 These findings also corroborate to another study by Okihara, et al 7 (2014), which found a memory impairment accompanied by low number of neuron cells in the hippocampus after long-term soft diet. 7 Previous studies on mastication impaired animal models through tooth extraction 22 , 23 , bite-raise 24 , 25 and long-term soft diets 7 , 26 found that these aspects may alter hippocampus learning and memory function. Other studies also proved that impaired function of the hippocampus due to long-term soft diet could be improved by providing a hard diet.…”
Section: Discussionmentioning
confidence: 99%
“…Reduced masticatory abilities due to periodontal disease may result in dietary deficiencies and increased stress response, and these may lead to increased amyloid beta (Ekuni, et al, 2013). It is also possible that the relationship between CAL and amyloid load is related to a relationship between CAL and cognitive dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Aged ApoE −/− mice showed significantly impaired cognitive function, which may be caused by a decreased neuronal excitability in hippocampus [15]. However, other studies did not detect learning and behavioral defects in ApoE −/− mice [16] and rats [17]. …”
Section: Introductionmentioning
confidence: 99%